Sums Within Sums!

S k = k = 0 1 ( 4 k + 1 ) ( 4 k + 3 ) S n = n = 1 ( 1 ) n + 1 n 2 S w = w = 0 ( 1 ) w 2 w + 1 \begin{aligned} S_k & = \sum_{k=0}^\infty\frac{1}{(4k+1)(4k+3)} \\ S_n & = \sum_{n=1}^{\infty} \frac{(-1)^{n+1}}{n^{2}} \\ S_w & =\sum_{w=0}^{\infty} \frac{(-1)^{w}}{2w+1}\end{aligned}

For S k S_k , S n S_n and S w S_w as defined above, find i = 1 S k S n i 2 S w \displaystyle \sum_{i=1}^{\infty} \frac{S_k}{S_ni^{2}}-S_w .


The answer is 0.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Chew-Seong Cheong
Sep 25, 2018

S k = k = 0 1 ( 4 k + 1 ) ( 4 k + 3 ) By partial fraction decomposition = 1 2 k = 0 ( 1 4 k + 1 1 4 k + 3 ) = 1 2 ( 1 1 1 3 + 1 5 1 7 + 1 9 1 11 + ) By Maclaurin series: = 1 2 k = 0 ( 1 ) k 2 k + 1 tan 1 x = k = 0 ( 1 ) k x k 2 k + 1 = tan 1 1 2 = π 8 \begin{aligned} S_k & = \sum_{k=0}^\infty \frac 1{(4k+1)(4k+3)} & \small \color{#3D99F6} \text{By partial fraction decomposition} \\ & = \frac 12 \sum_{k=0}^\infty \left(\frac 1{4k+1} - \frac 1{4k+3} \right) \\ & = \frac 12 \color{#3D99F6} \left(\frac 11 - \frac 13 + \frac 15 - \frac 17 + \frac 19 - \frac 1{11} + \cdots \right) & \small \color{#3D99F6} \text{By Maclaurin series:} \\ & = \frac 12 \color{#3D99F6} \sum_{k=0}^\infty \frac {(-1)^k}{2k+1} & \small \color{#3D99F6} \tan^{-1} x = \sum_{k=0}^\infty \frac {(-1)^kx^k}{2k+1} \\ & = \frac {\tan^{-1} 1}2 = \frac \pi 8 \end{aligned}

S n = n = 1 ( 1 ) n + 1 n 2 = 1 1 2 1 2 2 + 1 3 2 1 4 2 + 1 5 2 1 6 2 + = 1 1 2 + 1 2 2 + 1 3 2 + 2 ( 1 2 2 + 1 4 2 + 1 6 2 + ) = 1 1 2 + 1 2 2 + 1 3 2 + 2 2 2 ( 1 1 2 + 1 2 2 + 1 3 2 + ) Riemann zeta function ζ ( k ) = n = 1 1 n k = ζ ( 2 ) 1 2 ζ ( 2 ) = 1 2 ζ ( 2 ) = π 2 12 Note that ζ ( 2 ) = π 2 6 \begin{aligned} S_n & = \sum_{n=1}^\infty \frac {(-1)^{n+1}}{n^2} \\ & = \frac 1{1^2} {\color{#3D99F6}- \frac 1{2^2}} + \frac 1{3^2}{\color{#3D99F6}- \frac 1{4^2}} + \frac 1{5^2}{\color{#3D99F6}- \frac 1{6^2}} + \cdots \\ & = \frac 1{1^2} + \frac 1{2^2} + \frac 1{3^2} + \cdots \color{#3D99F6} - 2 \left(\frac 1{2^2} + \frac 1{4^2} + \frac 1{6^2} + \cdots\right) \\ & = \frac 1{1^2} + \frac 1{2^2} + \frac 1{3^2} + \cdots \color{#3D99F6} - \frac 2{2^2} \left(\frac 1{1^2} + \frac 1{2^2} + \frac 1{3^2} + \cdots \right) & \small \color{#3D99F6} \text{ Riemann zeta function }\zeta(k) = \sum_{n=1}^\infty \frac 1{n^k} \\ & = \zeta(2) - \frac 12 \zeta(2) = \frac 12 \zeta(2) = \frac {\pi^2}{12} & \small \color{#3D99F6} \text{Note that }\zeta(2) = \frac {\pi^2}6 \end{aligned}

S w = w = 0 ( 1 ) w 2 w + 1 = tan 1 1 = π 4 \begin{aligned} S_w & = \sum_{w=0}^\infty \frac {(-1)^w}{2w+1} = \tan^{-1} 1 = \frac \pi 4\end{aligned}

Then

i = 0 S k S n i 2 S w = i = 0 π 8 π 2 12 i 2 π 4 = 3 2 π i = 0 1 i 2 π 4 = 3 2 π π 2 6 π 4 = π 4 π 4 = 0 \begin{aligned} \sum_{i=0}^\infty \frac {S_k}{S_ni^2} - S_w & = \sum_{i=0}^\infty \frac {\frac {\pi}8}{\frac {\pi^2}{12} \cdot i^2} - \frac \pi 4 = \frac 3{2\pi} \sum_{i=0} \frac 1{i^2} - \frac \pi 4 = \frac 3{2\pi} \cdot \frac {\pi^2}6 - \frac \pi 4 = \frac \pi 4 - \frac \pi 4 = \boxed 0 \end{aligned}

@Aidan Poor , n n should start at 1 \color{#D61F06}1 instead of 0 in S n = n = 1 ( 1 ) n + 1 n 2 \displaystyle S_n = \sum_{\color{#D61F06}n=1}^\infty \frac {(-1)^{n+1}}{n^2} .

Chew-Seong Cheong - 2 years, 8 months ago

Log in to reply

The error has been fixed. Thanks!

Aidan Poor - 2 years, 8 months ago

Why t a n 1 1 = π 4 tan^{-1} 1=\frac{\pi}{4} while t a n 1 1 2 = ( π ) 2 8 \frac{tan^{-1} 1}{2}=\frac{(\pi)^2}{8} .Or,in short form,why π 4 × 1 2 = ( π ) 2 8 \frac{\pi}{4} \times \frac{1}{2}=\frac{(\pi)^2}{8} ?

Gia Hoàng Phạm - 2 years, 8 months ago

Log in to reply

Sorry, typo. It should be π 8 \frac \pi 8 .

Chew-Seong Cheong - 2 years, 8 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...